Taxas de alimentação para rã-touro com manejo alimentar automático e alta frequência alimentar - Castro, C. S.; Argentim, D. [UNESP]; Oliveira, L. C.; Zacarkim, C. E.; Agostinho, C. A. [UNESP] (Cordoba University Press (UCOPress), 2017)
Three feeding rates (3, 4 and 5% of body weight/day - BW/day) with automated feed management and high feeding frequency (24 meals/day) for bullfrogs (Lithobates catesbeianus) under wet systems were evaluated in this 60-day experiment. Bullfrogs with an average weight of 31.91±0.97 g, were distributed into twelve 20 m2 wet pens at a density of 60 frogs/m2. Commercial extruded feed for carnivorous fish was supplied directly onto water surface by automatic feeders. At 20 and 40 days of the experiment, the best growth was observed in frogs treated with a feeding rate of 5% BW/day. The frogs reached an average weight of 100.2 g at the end of the experiment but there was no difference among the feeding rates. At the end of the experiment, feeding rates of 3, 4 and 5% BW/day resulted in apparent feed conversion values of 1.08, 1.56 and 1.52, respectively, which are considered excellent for frog rearing. Bullfrogs reared at ideal temperature and with an average weight of 31.9 to 87.6 g can be fed at a high feeding rate (5% BW/day) for a greater growth. When temperature is lower than 25°C, feeding rate of 3% BW/day could be considered the most suitable for bullfrog weighing from 87.6 to 100.2 g, because the feed conversion ratio was numerically better and reduced feed leftovers.
Feeding rates for bullfrogs with automated feed management and high feeding frequency
Keywords: Automatic feeding; Lithobates catesbeianus; Wet system